Smoking Prevention in Indonesian Schools: Policy Opportunities in the Perspective of the Kingdons Multiple Streams Framework - Roni Gunawan; Hardisman Hardisman (International Journal Of Health Science, 2025)
The prevalence of smoking among children and adolescents (school age) in Indonesia continues to increase, even though there have been various regulations such as Permendikbud No. 64 of 2015 and PP 109 of 2012. This fact indicates that schools are not yet able to become a safe and free environment from cigarette exposure. This study aims to analyze the dynamics of school-age smoking prevention policies using the Kingdon’s Multiple Streams Framework (MSF), which identifies three major currents in policy: problem, policy, and politics. Through an integrative literature review approach to various scientific sources and policies for the 2021–2025 period, this study found that problem and policy streams have been relatively strong, but political streams are still weak. The lack of political commitment, the strong influence of the cigarette industry, and the lack of ratification of the FCTC are the main obstacles to the opening of the policy window. The proposed strategy includes a softening up approach with a focus on preventing smoking in schools as a form of protecting the future generation of the nation, as well as coupling focusing events by utilizing viral events to suppress public opinion and policymakers. The role of policy entrepreneurs from academics, teachers, NGOs, and educational and health institutions is very crucial in uniting the three policy streams. This study encourages the birth of new policies that are more specific, evidence-based, and sustainable in protecting school children from the dangers of smoking.